2011
DOI: 10.2519/jospt.2011.3448
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyclic Loading Simulating Oscillatory Joint Mobilization on the Posterior Capsule of the Glenohumeral Joint: A Cadaveric Study

Abstract: Study Design Experimental laboratory design. Objectives To examine the effect of force and repetition during oscillatory joint mobilizations on the posterior capsule of the glenohumeral joint. Background The optimal external force and frequency to be used during joint mobilization to elongate the posterior capsule of the glenohumeral joint has yet to be identified. Methods Twenty-one posterior capsules were harvested from fresh-frozen shoulders. A cyclic loading test simulating oscillatory posterior joint mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…These results are in line with a previous in vivo study that evaluated GHJ capsular thickness and elasticity in two different positions, with an intra-rater reliability value of 0.93 for posterior-inferior capsule elasticity [12]. Previous studies reported ROM changes after mobilization [5,18] and tissue elongation after simulated oscillations [29], but a better understanding of how these interventions affect tissue properties is needed. This study demonstrated that SWE technology may allow non-invasive measurement of tissue changes during joint loading and capsule stretching procedures.…”
Section: A B Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in line with a previous in vivo study that evaluated GHJ capsular thickness and elasticity in two different positions, with an intra-rater reliability value of 0.93 for posterior-inferior capsule elasticity [12]. Previous studies reported ROM changes after mobilization [5,18] and tissue elongation after simulated oscillations [29], but a better understanding of how these interventions affect tissue properties is needed. This study demonstrated that SWE technology may allow non-invasive measurement of tissue changes during joint loading and capsule stretching procedures.…”
Section: A B Discussionsupporting
confidence: 89%
“…This is the first study to assess the reliability of SWE and correlations between the durometer and SWE for GHJ capsular tissue properties under clinically applicable tensile loads using cadaveric tissue to eliminate neuromuscular influences. Tensile loads were selected based on pilot testing of the durometer for capsular tissue with good reliability (ICC 3,5 , 0.87; 95% CI, 0.68 to 0.95) and a high correlation between the tensile load applied and durometer measurements for loads of 1, 2, and 5 kg, as well as other prior studies of GHJ tissue properties [17,18,29]. The SWE measurements for reliability and correlation in this study were performed by one observer in 1 day.…”
Section: A B Discussionmentioning
confidence: 99%
“…We consider that mobilization effec- tively led to such density decreases, as the treatment group showed significant improvement. Studies using shoulder joint specimens from fresh cadavers [6][7][8] reported that mobilization (repetitive stretch stimulation) increased the range of joint motion and altered the rigidity of the joint capsule. It is possible that only the cross-linking between collagen fibers was damaged, though we did not investigate cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…The joint capsule can be extended by mobilization 3) , and many recent clinical studies have reported its effectiveness when the range of joint motion is limited 4,5) . These studies in which the effectiveness was verified by basic medical examination reported results derived only from the examination of fresh cadavers [6][7][8] , which led to incomplete understanding of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…1 The glenohumeral posterior glide and distraction mobilizations have been well researched in regard to their ability to produce tissue deformation and stretch of the glenohumeral joint capsule. 5,[11][12][13] The posterior glide technique has demonstrated the ability to create significant accessory glenohumeral movement and capsular deformation utilizing Kaltenborn grade III mobilization forces. 11,12 Previous work has demonstrated that during posterior translational mobilizations, the posterior rotator cuff serves as a passive restraint resisting as much as 35% of the overall posterior force at 60° abduction in a cadaver model.…”
Section: Introductionmentioning
confidence: 99%